Place of refuge photos and research note: how the Mayo Clinic uses the serious leisure perspective within a mechanical and humanic environmental healthcare design to reduce stress. Issue 4 (1st October 2020) - Dieser, Rodney B.; Ziemer, Renee; Edginton, Christopher R.
ABSTRACT : The purpose of this research note is to directly build on the Dieser et al. (2017) study that summarized how the serious leisure perspective (SLP) present at the contemporary Mayo Clinic (Rochester, MN campus) can remedy patient stress and physician/medical staff burnout by creating enjoyable distractions, social support, self-determination and optimism through pleasant experience. This research note convenes on this previous study in two ways. First, to marshal photo elicit evidence by juxtaposing leisure activities (music, games and art) in the personal lives of Dr. Charles Horace Mayo (1865–1939) and Dr. William James Mayo (1861–1939) with these same leisure services offered for patients and staff at the contemporary Mayo Clinic. Second, to add a new contribution to the literature and underscore the integration of the SLP within mechanical and humanic environmental design features at the Mayo Clinic that has a purposeful consequence to decrease stress among patients (and medical staff) and create a place of refuge.